Detecção por RT-PCR em tempo real (TaqMan) e caracterização molecular parcial de vírus que infectam a videira - Dubiela, Carla Rosa (2012)
In recent years, Brazil has excelled in the production of grapes, either for fresh consumption or for processing. However, the occurrence of diseases is frequently mentioned as a threat to the viticulture, as it can cause significant damage to production and quality of grapes. Among the pathogens of the grapevine, viruses are outstanding because of the damage they can cause, which can compromise the economic viability of viticulture. About 60 viral species infect the grapevine; in Brazil, Grapevine leafroll-associated virus (GLRaV-1, -2, -3, -5 and -6), Grapevine virus A and B (GVA and GVB), Grapevine rupestris stem pitting-associated virus (GRSPaV), Grapevine fleck virus (GFkV) and Grapevine fanleaf virus (GFLV) have been detected. The application of tools for diagnosis of grapevine viruses are continually evolving, specifically for the real time RT-PCR, which is becoming more popular in viral diagnosis due to its advantages over conventional PCR. The objectives of this study were to evaluate the efficiency of TaqMan real-time RT-PCR, a variation that uses a fluorophore-labeled probe, for detection of ten important virus species that infect grapevine in Brazil: GLRaV-1 , -2, -3 and -5, GVA, GVB, Grapevine virus D (GVD), GRSPaV, GFkV and GFLV. Reactions targeted individual (simplex) or simultaneous (duplex and triplex) detections. Total RNAs from healthy grapevines and virus infected plants were used for presence/absence assays employing a commercial kit for performed reactions as One Step real-time RT-PCR. To validate this technique, 36 grapevine accessions, recovered after treatment of thermotherapy and tissue culture, have been indexed. It was possible to detect all above-mentioned viruses, with the exception of GLRaV-1, in simplex reactions from samples with multiple infections including different viral isolates, as well as in duplex assays GVA, GRSPaV, GLRaV-2 and GLRaV-3 (with probes labeled with the fluorophore VIC and quencher TAMRA) combined with GVB, GFLV, GFkV, GVD and GLRaV-5 (FAM / TAMRA). Virus detection in triplex reactions were successful only from cloned viral cDNA. After in indexing of the 36 grapevine accessions, the status of the tested plant materials can be considered satisfactory. Ten plants of each cvs. Cabernet Franc and C. Sauvignon, with and without symptoms of viral infection were evaluated agronomically. GRSPaV and GVB were detected in plants of both cultivars evaluated by real-time RT-PCR. Favourable values (with significant differences) were showed for many evaluated agronomic variables of asymptomatic plants. Additionally, aimed to: (a) to extend the molecular characterization of a local isolate of GFkV and (b) to perform the molecular characterization of local isolates of GVD and GLRaV-5. The amplified DNA fragments were cloned and sequenced. In addition to this characterization, 37 grapevine accessions were indexed for GFkV, GVD and GLRaV- 5 by real-time RT-PCR. Three DNA fragments of GVA and GLRaV-1, amplified by conventional RT-PCR with primers used in real-time RT-PCR reactions, were sequenced in an attempt to elucidate the partially negative results. The nucleotide sequences and deduced amino acids of the capsid protein gene (CP) of GFkV, the CP and the RNA binding protein of GVD and partial HSP70 (heat shock protein) gen of GLRaV-5 were obtained for local isolates. These viruses were detected in 20 (GVD), 7 (GLRaV-5) and 6 (GFkV) evaluated samples. The presence of GVD had not been reported previously in Brazil and GLRaV-5 was detected by serology only in São Paulo State. The sequence analysis of DNA fragments of GLRaV-1 and GVA allowed to propose explanations about some results. The TaqMan real-time RT-PCR brings sensitivity and specificity for viral diagnosis, being an important tool for indexing grapevine propagative materials, and efficiently detecting different viral species and isolates. The molecular characterization of isolates contributed to support the design of the primers and probes for higher efficiency of this technique.